Review of process-based nitrogen model for agricultural fields with implications for nitrogen simulations in stormwater BMPs. (May 2022) - Li, Jiayi; Culver, Teresa B.
Abstract: A process-based nitrogen model suitable for urban stormwater Best Management Practices (BMPs), when used as an extension to current stormwater models, can assist decision-making by predicting nitrogen removal performances. While such a model has not been created, process-based nitrogen modules for agricultural fields have been developed and applied. In this paper, the nitrogen modules in six agricultural models are reviewed in the perspective of assisting the development of a process-based nitrogen module for stormwater BMPs. The agricultural nitrogen modules have consistent structures and mathematical descriptions of biochemical reactions, but show more variety in incorporating environmental factors. The operational challenges, strengths, and weaknesses of simulating stormwater BMPs' nitrogen removal performances with current models are illustrated with a case study. Finally, suggestions on developing the process-based nitrogen module for stormwater BMPs are offered based on the review, the case study results, and the differences between the stormwater BMPs and agricultural fields. Highlights: Reviewed agricultural nitrogen modules from the perspective of developing process-based stormwater nitrogen modules. Assumptions, module structures, environmental factors, and biochemical reaction kinetics were listed annd compared. Challenges of simulating bioretention with current agricultural and stormwater models were illustrated with a case study. Specific suggestions were offered for establishing a more mechanistically accurate nitrogen model for stormwater BMPs.